Pengaruh Kemudahan Transaksi, Kemampuan Akses dan Layanan BSI Mobile terhadap Kepuasan Nasabah - Rahayu, Ranti; Effendi, Pranoto; Firmansyah (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This research aims to determine the impact of ease of transactions, access capabilities and BSI Mobile services on customer satisfaction (Study in the Sawangan Community - Depok). This research is quantitative research. The data obtained was based on a questionnaire distributed via Google Form to 100 respondents from the people of Sawangan District, Depok City. Using the SEM-PLS (Structural Equation Modeling - Partial Least Square) tool with the SmartPLS version 3 application, it conducts outer model and inner model testing. The results of the research show that all the three factors i.e. the ease of BSI Mobile transactions, the ability to access BSI Mobile, and the BSI Mobile service have positive and significant effects on customer satisfaction.